Building harmonious families among single mothers in rural East Java: A social resilience perspective - Eka Mariska Putri Imra; Febriandita Tedjomurti; Muhammad Faruki (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2026)
The phenomenon of single motherhood in many regions is marked by economic constraints, dual caregiving and breadwinning responsibilities, cultural stigma, and limited formal support, yet family harmony can still be maintained. This study analyzes how single mothers in rural Jombang build harmonious family resilience through multidimensional maternal agency, religious-spiritual resilience, and strategic adaptation to gender norms. Using a qualitative case study approach, data were collected through in-depth interviews, four weeks of observation, and source triangulation. The data were examined using Braun and Clarke’s reflexive thematic analysis, guided by Ungar’s social resilience framework. The findings reveal three key patterns. First, multidimensional maternal agency emerges from commitment to children, material and emotional support from extended families, and community involvement as socio-ecological resources that strengthen mothers’ resilience in facing socio-economic pressures. Second, religious-spiritual resilience is shaped by participation in religious communities, faith as a basis for life meaning, spiritual togetherness, and the reconstruction of maternal identity as a sacred trust in Islam. Third, agency within constraints is reflected in navigating gender roles, managing culturally rooted stigma, reconstructing family meaning around maternal responsibility, and facing unequal access to socio-ecological resources. The study concludes that rural single mothers’ resilience is formed through maternal agency, faith- and community-based spirituality, and strategic adaptation within structural constraints. Its policy contribution highlights the need to strengthen community social capital, empower religious institutions, and ensure equitable access to resources and social protection.